2021
DOI: 10.7759/cureus.20102
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Urinary Nephrin in Patients With and Without Diabetic Nephropathy and Its Correlation With Albuminuria

Abstract: IntroductionNephrin is a podocyte-specific protein that may serve as a urinary biomarker in patients with diabetic nephropathy. The objectives of the study were to determine urinary nephrin levels in patients with and without type 2 diabetic nephropathy and to assess the correlation between urinary nephrin and albuminuria. MethodsThis was a cross-sectional comparative study that was carried out at Jawaharlal Institute of Postgraduate Medical Education and Research (JIPMER), Puducherry over 18 months. Diabetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
(10 reference statements)
1
3
0
Order By: Relevance
“…Studies have shown that glomerular and tubular changes are strongly associated with the pathogenesis of DKD 24,25 . In line with this finding, podocyte and tubule biomarkers may predict the onset or progression of DKD [18][19][20] . Furthermore, accumulated evidence has demonstrated that urinary podocytes and tubular proteins can be positively correlated with hyperglycemia 26,27 , and interestingly, these levels are elevated even in normoalbuminuric patients with diabetes 25,28 .…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Studies have shown that glomerular and tubular changes are strongly associated with the pathogenesis of DKD 24,25 . In line with this finding, podocyte and tubule biomarkers may predict the onset or progression of DKD [18][19][20] . Furthermore, accumulated evidence has demonstrated that urinary podocytes and tubular proteins can be positively correlated with hyperglycemia 26,27 , and interestingly, these levels are elevated even in normoalbuminuric patients with diabetes 25,28 .…”
Section: Discussionsupporting
confidence: 69%
“…Herein, we revealed the nephroprotective action of AFA extract adjuvant to insulin, as indicated by the maintenance of baseline expression levels of mRNA (Nphs1, Nphs2, Wt1, and Lrp2) and protein (nephrin, podocin, WT1, and megalin) in the kidney tissue. Interestingly, nephroprotection was also evidenced through the www.nature.com/scientificreports/ reduction of urinary loss of nephrin, podocin, WT1, and megalin, given that these proteins are markers of kidney glomerular and tubular integrity, and their loss is typically associated with the onset of kidney dysfunction [18][19][20] . Nephrin and podocin are slit diaphragm-associated proteins involved in the maintenance of the glomerular filtration barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Correcting for age, partial correlation was conducted. A significant positive connection was found between albuminuria, the current gold standard, and the examined biomarkers urinary nephrin [ 25 ]. These results show that these biomarkers represent renal damage, either glomerular or tubular or both, and that they increase proportionally to the degree of renal damage.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the urinary nephrin proportionately increases from normoalbuminuria to macroalbuminuria. This might emphasize the role of podocyte metabolism in diabetic kidney disease [31][32][33].…”
Section: Nephrinmentioning
confidence: 93%